DEVELOPMENT OF AN ELECTRONIC VISUAL AID FOR MONOCULAR VISUAL IMPAIRED PATIENTS - Nirvenesh A/L Ravindran (2023)
The purpose of this research is to develop a working prototype of a visual aid for monocular visual impaired patients. Monocular visual impaired patients most commonly do not have the ability to obtain 3-dimensional visualization on their surroundings and have a reduced field of vison. The primary function of this prototype is to increase the field of vision by at least 20%, as it is the minimum gain of visual field based on previous studies and to enable them to have depth perception on their surroundings. The research was started by understanding the requirements of patients and healthcare professionals through surveys and interviews at Tun Hussein Onn Eye Hospital. A house of quality was then constructed to analyse the data that was obtained. A total of three phases of development of prototype was conducted to develop this prototype. Each phase of the development was separated into hardware and software, in terms of hardware, the designs were analysed and the suitable microcontrollers were developed. In terms of software, the algorithms for the field of vision and depth perception was focused. Each phase of development underwent feedback review from healthcare professionals. The final phase of the prototype was tested on real patients at the hospital with two setup apparatus to justify both the objective, it was found that the angle of field of vision has increased from an average of 110 degrees to an average of 176 degree, which is an increase in field of vision by 60% and the depth perception was evident for all 100% of patients that used the visual aid. A final cost analysis was also conducted to reduce and justify the current cost of the visual aid which costs less than RM750.00 which are cheaper than current treatment costs of monocular visual impairement in a year. In a nutshell, this research has successfully developed a costefficient visual aid for monocular visual impaired patients to have depth perception and a huge increase in the field of vision.